THE COMMERCIALIZATION OF EDUCATION IN THE PERSPECTIVE OF MAQĀṢID AL-SYARĪʻAH - Muflih Naufal; Syarifuddin Ondeng; Syahruddin Usman (Wasīlah: Journal Of Sharia Sciences, 2025)
This study critically analyzes the commercialization of education within Islamic educational institutions in Indonesia through the framework of maqāṣid al-sharīʻah. The scope of the study covers the forms, driving factors, and impacts of commercialization on access, educational quality, and the normative orientation of Islamic education. Employing a qualitative literature-based approach enriched with phenomenological analysis, the research draws upon academic publications, government reports, and relevant empirical findings. The results show that commercialization manifests through rising tuition fees, competitive educational marketing, and the commodification of curricula and additional services. These practices contribute to widening disparities in access, deepening quality gaps between institutions, and shifting the orientation of Islamic education from moral and spiritual formation toward market-driven objectives. Through maqāṣid al-syarīʻah analysis particularly the principles of preserving intellect (ḥifẓ al-‘aql), religion (ḥifẓ al-dīn), human dignity (ḥifẓ al-nafs), and wealth (ḥifẓ al-māl) this study finds that several commercialization practices contradict Islamic ethical principles and risk undermining the public character of education. The study concludes that Islamic education governance must be reformulated to balance financial sustainability with justice, inclusivity, and the preservation of core Islamic educational values.